2014
DOI: 10.1155/2014/130925
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Split Deswirl Vane in a Two-Stage Refrigeration Centrifugal Compressor

Abstract: This study numerically investigated the influence of using the second row of a double-row deswirl vane as the inlet guide vane of the second stage on the performance of the first stage in a two-stage refrigeration centrifugal compressor. The working fluid was R134a, and the turbulence model was the Spalart-Allmaras model. The parameters discussed included the cutting position of the deswirl vane, the staggered angle of two rows of vane, and the rotation angle of the second row. The results showed that the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Palmer [45] found that reduced first-stage diffusion could improve the surge range over 80% rotational speeds, but the improvement was limited with inducer shroud bleed. It has been observed that, at low mass flow rates, the de-swirler vane influences the upstream flow structure of the vaneless diffuser and return channel [46]. Hung [47] suggested that, in the case of a vaned diffuser, the vane angle must be increased to reduce the surge mass flow rate.…”
Section: Two Stagementioning
confidence: 99%
“…Palmer [45] found that reduced first-stage diffusion could improve the surge range over 80% rotational speeds, but the improvement was limited with inducer shroud bleed. It has been observed that, at low mass flow rates, the de-swirler vane influences the upstream flow structure of the vaneless diffuser and return channel [46]. Hung [47] suggested that, in the case of a vaned diffuser, the vane angle must be increased to reduce the surge mass flow rate.…”
Section: Two Stagementioning
confidence: 99%
“…Compared to axial inlet, the radial IC will introduce extra flow loss and distortion at the impeller inlet, which will negatively affect the performance of the compressor. 8,9 However, due to the nonaxisymmetric geometry of radial IC, a complex threedimensional internal flow is formed, making the flow measurements more difficult and time-consuming; while without detailed experimental data, the reliability of numerical simulations on such a complex geometry cannot be guaranteed. 10 Since the 1990s, benefiting from the development of aerodynamic probes and numerical methods, 11 the cost of experimental and numerical research on the flow field inside complex geometries have been greatly reduced, which promoted a thorough analysis of radial IC.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to axial inlet, the radial IC will introduce extra flow loss and distortion at the impeller inlet, which will negatively affect the performance of the compressor. 8,9 However, due to the non-axisymmetric geometry of radial IC, a complex three-dimensional internal flow is formed, making the flow measurements more difficult and time-consuming; while without detailed experimental data, the reliability of numerical simulations on such a complex geometry cannot be guaranteed. 10…”
Section: Introductionmentioning
confidence: 99%